Acute medicine: discharge lounge utilisation QI - James Larsen; Kaenat Mulla; Nasrin Moatamedi; Shahin Barati; George Tharakan (Future Healthcare Journal)
Background: Length of stay in the adult emergency department (ED) above 6 h is associated with increased 30-day mortality.1,2 To reduce ED length of stay of medical patients, the acute medical unit (AMU) must have capacity to admit medical patients in ED. The current 4-h performance for AMU at St Mary’s Hospital (SMH) is ∼20% for this financial year. The NHS 4-h target is 76%.1 Problem statement: AMU capacity at SMH currently sits at 98% daily, with an average discharge time of 15:24 h. Therefore, there is limited capacity to admit patients through the ED within 4 h. To reduce the average discharge time, AMU should transfer all eligible patients to the discharge lounge once discharge is agreed. This will create capacity earlier in the day for medical referrals and reduce overcrowding within the ED. The current discharge utilisation for AMU is 19% and discharge by noon is 13%. Organisational and strategical alignment: The Trust aim is to discharge 33% of patients by midday to ensure that patients can flow through the hospital safely.Vision: AMU at SMH to increase discharge lounge utilisation to reduce ED length of stay, thus improving patient experience and outcomes (Fig 1). SMART Aim: AMU to increase average discharge lounge utilisation to 40% for AMU within 6 months (Fig 2).Primary outcome measure: discharge lounge utilisation (%): improving.Balancing measures:• Discharge by noon (DBN %): improving• 4-h performance (AMU): improving• 12-h performance (AMU): improving